Institute of Visual Computing at the Bonn-Rhine-Sieg University of Applied Sciences, Germany - Goebbels, Gernot; Göbel, Martin; Hinkenjann, André; Heiden, Wolfgang; Winzker, Marco; Herpers, Rainer; Scholl, Robert (Journal on Interactive Systems, 2011)
This paper presents the newly founded Institute of Visual Computing at the Bonn-Rhine-Sieg University of Applied Sciences in Sankt Augustin, Germany. The research focuses as well as an overview of current projects are going to be part of this presentation.